Cerebellar atrophy and its contribution to cognition in frontotemporal dementias. Issue 1 (14th August 2018) - Chen, Yu; Kumfor, Fiona; Landin‐Romero, Ramon; Irish, Muireann; Hodges, John R.; Piguet, Olivier
Abstract : Objective: Increasing evidence suggests that cerebellar damage impacts on cognitive functions. Frontotemporal dementias (FTDs) are neurodegenerative brain conditions, primarily affecting the frontal and/or temporal lobe. Three main phenotypes are recognized, each with a distinct clinical and cognitive profile: behavioral‐variant FTD (bvFTD), semantic dementia (SD), and progressive nonfluent aphasia (PNFA). The severity of cerebellar changes and their relation to cognition in FTD, however, remain unclear. This study aimed to establish cerebellar gray matter changes on magnetic resonance imaging (MRI) and their relation to profiles of cognitive deficits in FTD subtypes. Methods: Ninety‐six FTD patients (45 bvFTD, 28 SD, and 23 PNFA), meeting current clinical diagnostic criteria, and 35 age‐, sex‐, and education‐matched controls underwent brain MRI and cognitive assessment. Cerebral and cerebellar gray matter integrity were investigated using voxel‐based morphometry. Results: Compared with controls, widespread bilateral cerebellar changes were observed in all FTD subtypes, with the greatest atrophy present in bvFTD. Significant associations were found between cerebellar integrity and cognitive performance in attention and working memory in bvFTD, visuospatial function in SD, and language‐motor function in PNFA. Bilateral atrophy of crus and lobule VI were most commonly associated with cognitive deficits, irrespective of FTD phenotype. Interpretation: This study is the first to identify distinct patterns of cerebellar atrophy across FTD syndromes, which in turn relate to discrete cognitive dysfunctions, after accounting for the effect of cerebral atrophy. These findings extend our understanding of the cerebellum and point to its involvement across an array of processes beyond the domain of motor function. Ann Neurol 2018;83:98–109